Divergent pathways in urban residents’ emergency behavior in China: a social cognition theory perspective based on a survey of 6,817 individuals across 72 communities - Wang, Chao; Zhao, Haocun; Zhang, Yijue; Shi, Ruyi (Frontiers in Public Health, 2025)
IntroductionFor communities to effectively reduce disasters, the mobilization and guidance of urban residents’ emergency behavior are essential. Community disaster reduction efforts can become more targeted and accurate when the different influencing factors behind different types of emergency behavior are clearly understood.MethodsWe classify emergency behavior into two categories—self-help and mutual aid—based on differences in residents’ behavioral motivations. A coupled “cognition-environment-behavior” driving model has been constructed, drawing upon social cognition theory, to study the mechanisms that drive residents’ emergency actions. The research empirically analyzes factors influencing residents’ emergency behavior during community disasters, utilizing a sample dataset from 72 communities across China that included 6,817 participants.ResultsThree findings are obtained from this study. (1) The extent of residents’ emergency knowledge and skills, with the public dissemination of community information, significantly affects the adoption of self-help emergency behavior. (2) Emergency emotional states, alongside community cultural propaganda, tend to promote mutual aid emergency behavior. (3) Experience with disasters significantly moderates how the community’s disaster mitigation environment affects residents’ emergency behavior.DiscussionThis study not only emphasize key differences in factors across various types of resident behavior but also offer theoretical direction and practical points of reference for enabling targeted responses in community disaster mitigation.